2009
DOI: 10.1007/s00018-009-8574-z
|View full text |Cite
|
Sign up to set email alerts
|

Different carbon sources affect lifespan and protein redox state during Saccharomyces cerevisiae chronological ageing

Abstract: Abstract. In this study, a proteomic approach that combines selective labelling of proteins containing reduced cysteine residues with two-dimensional electrophoresis/mass spectrometry was used to evaluate the redox state of protein cysteines during chronological ageing in Saccharomyces cerevisiae. The procedure was developed on the grounds that biotinconjugated iodoacetamide (BIAM) specifically reacts with reduced cysteine residues. BIAM-labelled proteins can then be selectively isolated by streptavidin affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…5C), confirming what recently observed by other authors (Le Moan et al, 2006;Magherini et al, 2009;McDonagh et al, 2009). Our results globally indicated that thiol oxidation could coordinate the metabolic response to herbicide-induced oxidative stress and regulate fluxes of carbohydrates (McDonagh et al, 2009); this could eventually have, in turn, negative relapses on the fermentative performance of yeasts.…”
Section: Redox-proteomic Analysis Of Herbicide-induced Oxidation Of Psupporting
confidence: 91%
“…5C), confirming what recently observed by other authors (Le Moan et al, 2006;Magherini et al, 2009;McDonagh et al, 2009). Our results globally indicated that thiol oxidation could coordinate the metabolic response to herbicide-induced oxidative stress and regulate fluxes of carbohydrates (McDonagh et al, 2009); this could eventually have, in turn, negative relapses on the fermentative performance of yeasts.…”
Section: Redox-proteomic Analysis Of Herbicide-induced Oxidation Of Psupporting
confidence: 91%
“…ROS may cause reversible and/or irreversible modifications on protein targets. Cysteine residues, for example, exist not only in fully reduced form (\SH) but also in different oxidation states that are partly reversible and can change relatively to the cell's redox state [6][7][8]. The introduction of carbonyl groups into proteins is another oxidative, non-enzymatic modification that occurs either as a result of direct attack by ROS or indirectly, through peroxidation of lipids that further attack protein acid residues [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CR in S. cerevisiae significantly protects against glutathione oxidation in young cells 26,31,32 and also decreases protein cabonylation. 32,33 Altogether, these data suggest CR in yeast prevents ROS accumulation, leading to lower levels of protein oxidation during chronological aging.…”
Section: Effects Of Cr On Redox State In Less Complex Model Organismsmentioning
confidence: 98%